Exploring automotive supplier data in life cycle assessment – Precision versus workload. (April 2022) - Oliveira, Felipe Bitencourt de; Nordelöf, Anders; Sandén, Björn A.; Widerberg, Anna; Tillman, Anne-Marie
Abstract: The International Material Data System (IMDS) can be used as data source for life cycle assessments (LCAs) in the automotive industry. The level of data aggregation and degree of completeness affect precision of LCA results and required workload. This paper assesses this trade-off. Life cycle impact assessment scores for an engine, modelled as detailed as possible, were compared to results for seven simplified modelling options. The study concludes that: (1) employing IMDS data with lower resolution reduced the workload marginally; (2) cutting-off materials below 1 wt-% greatly decreased workload while maintaining reasonable precision; (3) decreasing the number of substances representing each material largely affected scores for most impact categories except a few, including the climate change category, while (4) excluding complementary data for manufacturing significantly impacted greenhouse gas emissions. Since modelling choices affect the impact categories differently, aligning choices with the purpose of the study and available workload is paramount.